Learners' Attitude towards Mathematics, Technology on Their Mathematics Interest: The Mediating Role of Learners' Mathematics Perception - Yeribatuah, Peter; Arthur, Yarhands Dissou (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
This research work surveyed inquired into, and scanned carefully, the exhibiting indirect causation of learners’ mathematics perception, a connection jointly engaging learners’ stance towards mathematics and technology on their mathematics interest. This inquest was conducted on 200 Senior High School learners sampled in the Central part of Ghana. The employment of a survey and comprehensive questionnaire was necessitated. Amos Software (v. 23) was instrumental in the Modeling analysis computations (SEM: EFA/CFA), and the paths were tested on the hypotheses. Attitude towards mathematics produced a positive impact on learners’ interest, which in turn impacted positively on learners’ perception of mathematics, and technology yielded a positive impact on how learners perceive mathematics. There was a complete mediation of learners' perception of mathematics in the association between learners' attitudes towards mathematics and their interest in mathematics. Further studies could be carried out on the parameters using other methods to inquire about the impact of learners' attitudes on mathematics and the technology involved in their learning on their mathematics interests. The education system must be mindful of learners' attitudes, perceptions, and technology in their learning process. Colleges of education must bring up teachers in the light of learners' attitudes, perceptions, and technology in their learning and the appropriate pedagogy in their delivery of lessons. DOI: https://doi.org/10.22342/jpm.17.3.22103.361-378